Addition of interleukin 1 (IL1) and IL17 soluble receptors to a tumour necrosis factor α soluble receptor more effectively reduces the production of IL6 and macrophage inhibitory protein-3α and increases that of collagen in an in vitro model of rheumatoid synoviocyte activation. Issue 8 (1st August 2002) - Chevrel, G; Garnero, P; Miossec, P
Abstract : Objectives: To evaluate the usefulness of combination treatment with cytokine inhibitors. Methods: A simplified model was set up to evaluate the effect of tumour necrosis factor α (TNFα) soluble receptors (sTNFR) used alone and in combination with soluble interleukin 1 receptor (sIL1R) and sIL17R on the production of markers of inflammation (IL6), of migration of dendritic cells (macrophage inhibitory protein-3α (MIP-3α)), and of matrix synthesis (C-propeptide of type 1 collagen (P1CP)). Synoviocytes were stimulated with supernatants of activated peripheral blood mononuclear cells (PBMC) from patients with rheumatoid arthritis (RA). Soluble receptors (sR) were preincubated at 1 γg/ml alone or in combination with the supernatants before addition to RA synoviocytes. IL6, MIP-3α, and P1CP production was measured by enzyme linked immunosorbent assay (ELISA) in 48 hour synoviocyte supernatants. Results: IL6 production decreased by 16% with sTNFR alone compared with no sTNFR (p<0.001) and by 41% with the combination of the three sR (p<0.001). MIP-3α production decreased by 77% with sTNFR alone compared with no sTNFR (p<0.001) and by 98% with the combination of the three sR (p<0.001). In the presence of sTNFR alone, P1CP production increased by 25% compared with no sR (p<0.01). The combination of the three sR increased P1CP production by 48% (p<0.01). Conclusion: The effect of sTNFR on IL6, MIP-3α, and P1CP production by RA synoviocytes stimulated by activated PBMC supernatants was further enhanced when combined with sIL1R and sIL17R.